Population differences in performance on Relational Match to Sample (RMTS) sometimes reflect differences in inductive biases alone. (February 2021) - Kroupin, Ivan; Carey, Susan
Abstract : A much replicated finding is that only humans above the age of five succeed spontaneously on Premack's Relational Match to Sample task, which has been widely used in the comparative and developmental literatures to probe relational reasoning capacities. We review four different types of explanations for the failures of young children and non-human animals, two that posit capacity limitations and two that posit differences in learning histories alone. We review training studies that rule out capacity limitations, at least for crows, parrots, four-year-old children, and a variety of primate species. Finally, we review recent studies demonstrating that population differences sometimes reflect differences in inductive biases alone and discuss the crucial importance of inductive biases in relational reasoning.